1978
DOI: 10.1254/jjp.28.457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diltiazem on Guinea Pig Portal Vein in Hypertonic Solution

Abstract: Abstract-Effects of diltiazem were investigated on the isolated portal vein of the guinea pig in hypertonic solution. Hyperosmolarity was produced by sucrose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In isolated myocardium (7,8) and vascular (9)(10)(11)(12) or intestinal (13)(14)(15)(16) smooth muscles, it has been reported that this compound antagonizes calcium ion which is essential for muscle contraction, thus producing a decrease in the contractile force. Such a calcium antagonistic property of diltiazem has been shown in isolated pancreatic B-cell (1): the glucose-induced insulin secretion from the isolated islets of Langerhans from rats was suppressed by diltiazem and this effect was counteracted by increasing extracellular concentration of calcium ion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In isolated myocardium (7,8) and vascular (9)(10)(11)(12) or intestinal (13)(14)(15)(16) smooth muscles, it has been reported that this compound antagonizes calcium ion which is essential for muscle contraction, thus producing a decrease in the contractile force. Such a calcium antagonistic property of diltiazem has been shown in isolated pancreatic B-cell (1): the glucose-induced insulin secretion from the isolated islets of Langerhans from rats was suppressed by diltiazem and this effect was counteracted by increasing extracellular concentration of calcium ion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that diltiazem produced potent relaxing effects on the constrictor responses of various isolated vascular strips to spasmogens (9)(10)(11)(12). The concentration of diltiazem which inhibited the contraction of these vascular preparations by 50% was less than 10-6 M. On the other hand, a dose of 10-5M of diltiazem was required to induce a similar degree of inhibition in glucose-induced insulin secretion, as shown in the preceding in vitro (1) and present perfusion experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the Ca2+ influx by diltiazem has been suggested in experiments with mecha nical and electrical activities of the isolated guinea pig portal vein (8). On the other hand, Greenberg et al (9) …”
mentioning
confidence: 99%
“…relaxes the vascular smooth muscle (4,10) and reduces the myocardial contractile force (5) due to its calcium antagonistic property. It has been reported that the va-,odilating activity of diltiazem was not the same among various vascular smooth muscles, being more potent in the coronary artery than in the thoracic aorta and femoral artery (10).…”
Section: Diltiazemmentioning
confidence: 99%
“…Diltiazem is a potent coronary vasodilator with calcium antagonistic activity (1)(2)(3)(4)(5). Among various vascular beds tested, the vasodilating effect of diltiazem was especially remarkable in the coronary and vertebral arteries (6,7).…”
mentioning
confidence: 99%